2008
DOI: 10.4321/s1886-36552008000200006
|View full text |Cite
|
Sign up to set email alerts
|

A pilot survey on perceptions and knowledge of generic medicines among consumers in Penang, Malaysia

Abstract: ObjectiveTo explore the consumers’ perceptions and knowledge towards issues surrounding generic medicines utilization in Penang, Malaysia.MethodsA cross sectional survey was conducted with consumers who attended the annual University open day. Using convenience sampling, survey forms were distributed to the respective consumers via the help of a group of trained 1st year pharmacy students. For a period of 5 days, 400 respondents had participated in the survey. Analysis of the response from the collected forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 8 publications
2
62
0
5
Order By: Relevance
“…(2008). 28 When consumers believe that the effectiveness of generic medicines is less than their original brand equivalents, they are less likely to accept generic medicines or generic substitution. 19,27,29 Additionally, older consumers and those with lower levels of education are less likely to accept generic substitution.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…(2008). 28 When consumers believe that the effectiveness of generic medicines is less than their original brand equivalents, they are less likely to accept generic medicines or generic substitution. 19,27,29 Additionally, older consumers and those with lower levels of education are less likely to accept generic substitution.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…14 The majority of consumers learn about generic medicine from a physician, and this medical advice is critical to consumer's decision to take generic medicine. 15 In present study, majority of participants did not know about generic medicine and its implications, nor clinicians prescribe generic medicines. Generic medicines are cheaper alternative of innovator product and clinicians were not fully convinced that generic medicines are equivalent to branded ones, which can be reason for this negative response.…”
mentioning
confidence: 62%
“…Earlier, it was reported that the assessment of awareness level is always a preferable marker to judge the community's knowledge, attitude and practices regarding the safe utilization of drugs, which generally represents public decision to seek the healthcare facilities, and use of medicines, and finally the success of treatments (Al-Gedadi et al, 2008;Shah et al, 2011). Furthermore, efficacy of medicines is very significant term because it defines the tendency of any medicine to produce the required effect.…”
Section: Discussionmentioning
confidence: 99%
“…The expiry date for pharmaceuticals is the point in time when a product is no longer within an acceptable condition to be considered effective as well as safe for health of consumers (Al-Gedadi et al, 2008;Shah et al, 2011). Depending on the product, the expiry date may be set as a fixed time after .…”
Section: Introductionmentioning
confidence: 99%